(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Traction Is Part Of The Evidence Based Manual Physical Therapy Management Due To Its Mechanical Nature. The Efficacy Of Lumbar Traction (Lt) Has Been Established, Lt As The Most Used Method Of Spinal Decompression Therapy (Sdt) Reduces The Intradiscal Pressure And Vertically Increases The Intervertebral Space And Restore Disc Height Allowing Nutrients And Oxygen Supply To The Disc. While Lt Had Recently Been Used As A Conservative Treatment For Chronic Lumbar Disc Herniation (Cldh), Combined Lumbar Traction With Cervical Traction (Cltct) As One Intervention Which Has Been Suggested By (Al-Qudah, M.K) Was Used As A Part Of Rehabilitative Program In Patients With Cldh. Therefore, The Effectiveness Of Cltct Separately At Any Other Interventions Remains Absolutely Unclear And Uncertain. Objective: The Aim Of The Presented Work Is To Identify The Effectiveness Of Cltct [(Positional Sustained Lumbar Traction (Pslt) Combined With Mechanical Sustained Cervical Traction (Msct) As One Intervention] On Patients With Moderate (L4-L5) (L5-S1) Cldh, And To Compare Cltct With Traditional Mechanical Lumbar Traction (Mlt). Methods: In This Study, Twelve Outdoor Male Patients Diagnosed With Magnetic Resonance Imaging (Mri), Had Accepted To Participate The Study. They Were Chosen From Al-Karak Governmental Hospital, From 20th Of December To 1st February 2021. Subjects Were Divided Randomly In To Two Groups, Experimental Group (N=6) Performed Cupping Massage (Cm), Cltct And Core Stabilization Exercise (Cse), While The Control Group (N=6) Performed Cm, Mlt And Cse. All Subjects Were Advised To Perform The Cse Three Times Daily As A Home Program In Addition To One Set During Each Session Under The Therapist Supervision. All Subjects Had Exposed (18) Sessions For (6) Weeks. The Results Were Analyzed Using The Spss System. Results: Indicates That There Was Statistically Significant Difference Between The Pre And Post Measurements In Both Groups In Favor Of The Post Measurements In Term Of Pain And Disability. Also Results Indicate That There Was Statistically Significant Difference Between The Groups In Favor Of Experimental Group. Conclusions: The Present Study Demonstrates That The Use Of Cltct Has A Positive Effect On Patients With Cldh More Than Mlt.